Baptism by fire : eight presidents who took office in times of crisis - Updegrove, Mark K. (New York : Thomas Dunne Books, 2009)
Presents accounts of eight U.S. presidents who assumed office at times of crisis and how they met high-stakes challenges, from Lincoln's efforts on behalf of a divided nation and FDR's strategies during the Depression to Truman's inheritance of World War II and Kennedy's role in addressing the Cold War.
George Washington : the first -- Thomas Jefferson : "We are all Republicans, we are all Federalists" -- John Tyler : the accidental president -- Abraham Lincoln : "The Union is unbroken" -- Franklin D. Roosevelt : nothing to fear -- Harry S. Truman : "If you pray, pray for me now" -- John F. Kennedy : "The torch has been passed" -- Gerald R. Ford : "Our long national nightmare is over".
Includes bibliographical references (p. 273-278) and index.
Keywords: Presidents -- United States -- History; Crisis management in government -- United States -- History; Political leadership -- United States -- History; Presidents -- United States -- Biography